MAKAM-MAKAM TUA DI NAGARATENGAH, CINEAM, KABUPATEN TASIKMALAYA - Oerip Brahmantyo Boedi (Kemendikbud, 2019)
Nagaratengah Village, Cineam subdistrict, Tasikmalaya Regency in the past have a significant role. In the past, the village was once the capital of Galuh (Ciamis) Regency before it was transferred to Imbanagara. In Imbanagara, the center of Government was named Barunay, this name is the name of the center of Government while in Nagaratengah. As the center of Government, in Blok Barunay there are historicalarchaeological remains, such as the tomb of Raden Adipati Aryadikusumah, Raden Arya Panji Subrata, and Pangeran Arya Panjikusumah. Around this location there are suspected archaeological remains, such as Kyai Malanggedang's tomb and other tombs. The existence of these tombs should be examined about its shape, age, and location. Thus the study aims to answer these three things. The method for obtaining an appointment is to conduct a library study, observe directly in the field, and conduct interviews with selected speakers. Based on the study, there is an overview of old tombs with markers of upright rocks at the top or top of the hill. The tombs are derived from the same period, namely Islamic period, at the end of the Nagaratengah kingdom.